2020
DOI: 10.1002/cbin.11372
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‐103a‐3p suppresses lipopolysaccharide‐induced sepsis and liver injury by regulating FBXW7 expression

Abstract: Inflammation, apoptosis, and oxidative stress are involved in septic liver dysfunction. Herein, the role of miR‐103a‐3p/FBXW7 axis in lipopolysaccharides (LPS)‐induced septic liver injury was investigated in mice. Hematoxylin‐eosin staining was used to evaluate LPS‐induced liver injury. Quantitative real‐time polymerase chain reaction was performed to determine the expression of microRNA (miR) and messenger RNA, and western blot analysis was conducted to examine the protein levels. Dual‐luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Zhou and Xia reported high levels of miR-103a-3p in the liver and serum of LPS septic mice and also in human patients. In vitro miR-103a-3p inhibition suppressed LPS-induced inflammation by downregulating the expression of TNF, IL-1β and IL-6 in vitro and in vivo [ 232 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhou and Xia reported high levels of miR-103a-3p in the liver and serum of LPS septic mice and also in human patients. In vitro miR-103a-3p inhibition suppressed LPS-induced inflammation by downregulating the expression of TNF, IL-1β and IL-6 in vitro and in vivo [ 232 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, miR-103a-3p and miR-214 play an important role when SPPA inhibits oxidative ovarian damage. Zhou et al had reported that interfering with miR-103a-3p is able to inhibit LPS-induced hepatocyte apoptosis, in ammation and oxidation reactions [20]. Cheng et al found that upregulation of miR-103a-3p promoted chondrocyte proliferation of human osteoarthritis (OA) and inhibited cell apoptosis and in ammatory responses [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the knockdown of TUG1 reversed the damage of LPS. Besides oxidative stress, apoptosis is also accompanied by LPS-induced inflammation ( Chen et al, 2017 ; Lv et al, 2020 ; Zhou and Xia, 2020 ). We further detected apoptotic marker proteins cleaved-caspase 3, Bax, and Bcl 2 in LPS-treated cells, which indicated that silencing TUG1 inhibited LPS-induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%